PEMAHAMAN PESERTA DIDIK TERHADAP PENDIDIKAN MANUSIA SECARA UTUH DAN KRISTIANI DI SMAK ST. AUGUSTINUS KEDIRI - Yohanes Ega Satriyo; Agustinus Supriyadi (Bahasa Indonesia, 2019)
The whole human education includes: physical, spiritual, intellectual, sosial, moral and sexual aspects. Genrrally, the whole human education is seen as fostering physical and spiritual aspects. Gravissimum Educationis says that Christian education is also the whole human education in which the implementation is based on the spirit of gospel and Jesus Christ. Through Christian education, the students are provided various knowledges and preverences of life so that, they can participate to realize the public welfrare and the ultimate goal of salvation. The development of a more and instant time has led to various aspects of life, including the process of education.The succes meaning of an education that should be emphasize the process, has sifted in meaning. The shifting meaning is evident from the efforts of the school or students who persue only academic values in a report of learning outcomes. In this regard, SMAK St. Augustinus Kediri, is one of Catholic educational institutions that must provide the whole and Christian human education. The issues that arise are: How is student's understanding on the wholeand Christian human education?How is the whole and Christian human education carried at SMAK St. Augustine Kediri? Based on the problems, the aim of this study is to describe students' understanding on the whole and Christian human at SMAK St. Augustinus Kediri and describe the implementation of thewhole and Christian human educationat SMAK St. Augustine Kediri. Through qualitative research, interviews were conducted to 10 respondents of grade XII SMAK St. Augustine Kediri. The conclusion of the study are: first, students understand the meaning of the whole human education. Second, students understand the meaning of Christian education. Third, wholeand Christian human education has almost been implemented at SMAK St. Augustinus Kediri, but there are still some things that need to be improved.